Enhanced magnetic properties and anisotropy in hot-deformed Ce–Fe–B magnets by suppressing CeFe2 phase with Ga addition - Xuefeng Liao; Weiwei Zeng; Junwei Zheng; Zhiyu Liu; Cifu Lu; Renheng Tang; Qing Zhou (Journal of Materials Research and Technology, 2023)
Nanocrystalline Ce–Fe–B alloys exhibit potential utilization for low-cost permanent magnets, however, the preparation of anisotropic magnets with satisfactory magnetic properties remains a challenge. CeFe2 Laves phase with high melting point that forms in the Ce-rich Ce–Fe–B magnets has been considered as the reason to be detrimental to its hot-working process and magnetic performance. Herein, we report the significant effects of adding Ga to nanocrystalline melt-spun Ce17Fe78-xB6Gax alloys on suppressing the CeFe2 phase and enhancing coercivity. The x = 2.0 alloy is identified as the optimal precursor for preparing anisotropic hot-deformed magnet due to its lower CeFe2 phase content (5.7 wt.%), considerably less than that of the ternary Ce–Fe–B alloy (17.6 wt.%). The congruent alignment and platelet-shaped grain characteristics are obtained in the Ga-added hot-deformed magnet, indicating an enhanced anisotropy that results in an improved remanence from 4.2 kGs to 5.9 kGs. The development of such texture can be ascribed to the reduced amount of CeFe2 phase, allowing the formation of Ce-rich grain boundary (GB) phase, which is necessary to induce grain alignment during hot deformation process. Two types of Ga-containing GB phases are found in the Ga-added magnet, namely typical Ce-rich/Fe-lean GB phase and Ce6Fe13Ga phase. The uniformly distributed Ce-rich GB phases surrounding the main grains helps to magnetic isolate the Ce2Fe14B grains and thus enhance the coercivity, as verified by detailed microstructural characterizations combined with micromagnetic simulation. The work offers a potential way to realize anisotropy in Ce–Fe–B magnets and inspires further exploration of high abundance Ce-based magnets.